Foundation and chaos - Bear, Greg, 1951-; Benford, Gregory, 1941- (London : Orbit, 1999)
With the Empire in decline, brilliant robot R. Daneel Olivaw has been tapped to oversee the migration to Star's End, but his mission hits a snag when he discovers that other robots, as well as humans, are questioning his strategy.
Sequel to: Foundation's fear by Gregory Benford.
Publisher's Weekly
Wilson's Fiction
Adult.
Adult
Keywords: Artificial intelligence -- Fiction; Seldon, Hari (Fictitious character) -- Fiction; Artificial intelligence -- Fiction; Science fiction; Seldon, Hari (Fictional character) -- Fiction; Science fiction